Autonomous Navigation Of Micro Air Vehicle Using Ultra-Wideband Indoor Positioning In Precision Agriculture - Ching, Poh Ling (Universiti Sains Malaysia, 2021)
Micro air vehicles (MAVs) have penetrated precision agriculture domains over the past years due to their flexibility and capacity. However, the problem arises when moving the MAV applications into greenhouses, which limits the use of Global Positioning System (GPS). Visual methods have been recently utilized, but the sensors present limitations in greenhouses with the high amount of mist. The challenges remain in position accuracy and robustness in long-term autonomy. To this end, this project proposed a novel system to allow autonomous indoor navigation of MAV using ultra-wideband (UWB) technology. A UWB mobile tag is mounted on the MAV, which actively sending ranging request to a constellation of fixed-position anchors. The MAV is able to self-localize based on the distance measurements fused by an extended Kalman filter (EKF). The position estimation is fed into the control loop to aid the MAV navigation. Various flight tests were carried out successfully in different indoor environments. The results showed that the satisfactory performance of UWB autonomous navigation in greenhouses. The proposed system is expected to reduce labour-intensive activities and possible human error.